A cross-layer approach to timely responsive transmission under collection tree topology in wireless sensor network. (2015) - Tang, Yu; Bu, Changqin; Fan, Aihua
Collection tree protocol (CTP) provides a link quality-based routing schema for wireless sensor networks (WSNs) with a collection tree topology, under which the link quality is measured by throughput rather than transmission latency. Yet it is not appropriate for the applications that need to transmit packets in a timely manner. Furthermore, implementation of timely responsive service in WSNs demands real-time supports from both routing and transport control layer. In this paper, we propose a cross-layer approach in which the packets with transmission deadlines are routed via an average transmission time (ATT) protocol and the congestion control is imposed through a performance-differentiated packet dropping policy. Simulation experiments on the TinyOS platform show that ATT protocol outperforms CTP by reducing the transmission delay up to 17.7%, while maintains a slightly better transmission reliability measured by the packet loss rate. The proposed cross-layer approach presents a promising core feature of framework in delivering real-time service in WSNs.